Preoperative Anemia and Perioperative Outcomes in Gynecological Surgery: A Single-Center Retrospective Study - Zhang M; Yuan S; Yang X (International Journal of Women's Health, 2025)
Mengyu Zhang,1,* Shiqiong Yuan,2,* Xin Yang1 1Department of Obstetrics and Gynecology, Peking University People’s Hospital, Beijing, People’s Republic of China; 2Department of Obstetrics and Gynecology, Zhengzhou Muzhou Hospital, Zhengzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Yang, Department of Obstetrics and Gynecology, Peking University People’s Hospital, No. 11 Xizhimen South Street, Beijing, 100044, People’s Republic of China, Tel +86-13701318932, Email xinyang_2003@sina.comPurpose: To investigate the incidence and clinical characteristic of preoperative anemia and its impacts on perioperative outcomes in gynecological inpatients.Patients and Methods: We retrospectively collected data from surgical patients admitted to the Department of Gynecology at Peking University People’s Hospital between April 2023 and January 2024. The data included demographic information, preoperative laboratory tests, diagnoses, surgery records, and hospitalization information. Preoperative anemia was defined as hemoglobin (Hb) concentration less than 120 g/L according to the last blood test before surgery. The primary outcomes of this study were perioperative complications, including infection, heart failure, thromboembolic events, intestinal obstruction, and transfer to the intensive care unit (ICU). Secondary outcomes included perioperative RBC transfusion, length of stay (LOS) and hospitalization costs. Outcomes were compared between the anemic group and non-anemic group, and logistic regression analyses were used to identify risk factors associated with the study outcomes.Results: This study included a total of 2,519 patients, and the incidence of preoperative anemia was 30.8%. Compared with the non-anemic group, those in anemic group had younger age (44 vs 47, P < 0.001) and lower body mass index (BMI) (23.2 vs 23.9, P < 0.001); however, higher incidences of perioperative RBC transfusion (10.7% vs 1.7%, P < 0.001) and complications (4.4% vs 0.9%, P < 0.001), higher hospitalization costs (14531 vs 13681, P = 0.044) and longer LOS (6 vs 5, P < 0.001). According to multivariate analyses, lower BMI (aOR = 0.893, P = 0.016), having comorbidity (aOR = 4.422, P < 0.001), preoperative anemia (aOR = 6.259, P < 0.001), gynecological malignancy (aOR = 4.376, P < 0.001), longer surgery duration (aOR = 1.010, P < 0.001) and increased blood loss (aOR = 1.002, P < 0.001) were associated with higher incidences of perioperative complications. Based on final surgical pathology, we divided surgical patients into gynecologic malignancy and non-malignancy groups. Similar results were obtained in both groups, preoperative anemia remained a facilitating factor of perioperative RBC transfusion and complication. Additionally, we investigated whether patient blood management (PBM) before surgery could improve perioperative outcomes. The results revealed that preoperative RBC transfusion was a protective factor against perioperative complication (aOR = 0.032, P = 0.017), while the relationship between iron supplementation and perioperative complication remained unclear (aOR = 0.628, P = 0.502).Conclusion: Preoperative anemia was related to higher incidence of perioperative RBC transfusion and complication, and it increased hospitalization costs and prolonged LOS in gynecological inpatients. PBM before surgery could help improve perioperative outcomes. These findings emphasized the importance of early identification and active management of anemia, which might help reduce transfusion needs, minimize complications, and ultimately enhance gynecological inpatients’ outcomes.Keywords: anemia, patient blood management, perioperative complications, perioperative transfusion